2021
DOI: 10.1021/acsomega.1c01708
|View full text |Cite
|
Sign up to set email alerts
|

Biological Process of Alkane Degradation by Gordonia sihwaniensis

Abstract: With the development of the petroleum industry, oil pollution has become widespread. It is harmful to the digestive, immune, reproductive, and nervous systems of fishes, wild animals, and humans, causing severe threats to ecological safety and human health. Gordonia has increasingly attracted attention in the treatment of alkane pollution for its outstanding performance against hydrophobic refractory substances. However, the lack of knowledge about alkane uptake and degradation restricts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 42 publications
0
15
1
Order By: Relevance
“…Similar to AlkB, rubredoxin and rubredoxin reductase are required for the operation of CYP153. It was previously suggested that bacteria contain one of alkane hydroxylases, but it was shown that bacteria of the genera Alcanivorax , Dietzia , Rhodococcus , Nocardia , and Gordonia possess both AlkB and CYP153 simultaneously, which is possibly an indication of the interaction of these enzyme systems in alkane oxidation [ 18 , 55 , 56 , 58 , 59 , 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar to AlkB, rubredoxin and rubredoxin reductase are required for the operation of CYP153. It was previously suggested that bacteria contain one of alkane hydroxylases, but it was shown that bacteria of the genera Alcanivorax , Dietzia , Rhodococcus , Nocardia , and Gordonia possess both AlkB and CYP153 simultaneously, which is possibly an indication of the interaction of these enzyme systems in alkane oxidation [ 18 , 55 , 56 , 58 , 59 , 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the lowest concentration of cells (Figure 4D), the height and density of the emulsion are lower, and there is a higher percentage of clear lower phase. These results demonstrate that the cells have some emulsifying activity, even at lower concentrations, indicating that not all BS/BE produced is expelled to the culture medium, and a significant concentration is retained by the cells, either as a part of their cellular membrane or strongly attached to it [40,41,44]. As G. alkanivorans strain 1B was isolated from oil contaminated soils, such properties give it a clear evolutionary advantage, since membrane hydrophobicity would allow for easier access to the hydrophobic C-sources (e.g., hydrocarbons) abundant in oil.…”
Section: Cellular Emulsifying Activitymentioning
confidence: 91%
“…Cationic resin and anionic resin should be pretreated before use in inulin extraction according to the reported method with minor modification. 40 , 41 In order to ensure that inulin products met the food standards, it was required that the Jerusalem artichoke extract after desalination should be neutral, which could avoid the degradation of inulin. Therefore, in the process of desalination and decolorization, the ion-exchange resin was usually arranged in the order of strong alkali, strong acid, and weak alkali to ensure that the final liquid pH was close to neutral.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Therefore, the resin was usually rinsed with deionized water to remove impurities for pretreatment. Cationic resin and anionic resin should be pretreated before use in inulin extraction according to the reported method with minor modification. , In order to ensure that inulin products met the food standards, it was required that the Jerusalem artichoke extract after desalination should be neutral, which could avoid the degradation of inulin. Therefore, in the process of desalination and decolorization, the ion-exchange resin was usually arranged in the order of strong alkali, strong acid, and weak alkali to ensure that the final liquid pH was close to neutral. , According to the series mode of strongly basic anion-exchange resin, strongly acidic cation-exchange resin, and weakly basic anion-exchange resin, 400 mL of the ion-exchange resin is loaded into the column to form an ion-exchange column combination. , Three kinds of resins were used to test the desalination and decolorization effect of Jerusalem artichoke extract by measuring salinity, conductivity, and absorbance.…”
Section: Materials and Methodsmentioning
confidence: 99%